Cytokine responses in acute and persistent human parvovirus B19 infection - Isa, A (Blackwell Science Inc, 2007)
The aim of this study was to characterize the proinflammatory and T helper (Th)1/Th2 cytokine responses during acute parvovirus B19 (B19) infection and determine whether an imbalance of the Th1/Th2 cytokine pattern is related to persistent B19 infection. Cytokines were quantified by multiplex beads immunoassay in serum from B19-infected patients and controls. The cytokine responses were correlated with B19 serology, quantitative B19 DNA levels and clinical symptoms. In addition to a proinflammatory response, elevated levels of the Th1 type of cytokines interleukin (IL)-2, IL-12 and IL-15 were evident at time of the initial peak of B19 viral load in a few patients during acute infection. This pattern was seen in the absence of an interferon (IFN)-γ response. During follow-up (20–130 weeks post-acute infection) some of these patients had a sustained Th1 cytokine response. The Th1 cytokine response correlated with the previously identified sustained CD8(+) T cell response and viraemia. A cross-sectional study on patients with persistent B19 infection showed no apparent imbalance of their cytokine pattern, except for an elevated level of IFN-γ response. No general immunodeficiency was diagnosed as an explanation for the viral persistence in this later group. Neither the acutely infected nor the persistently infected patients demonstrated a Th2 cytokine response. In conclusion, the acutely infected patients demonstrated a sustained Th1 cytokine response whereas the persistently infected patients did not exhibit an apparent imbalance of their cytokine pattern except for an elevated IFN-γ response.